Three‐year outcomes and reconnection patterns after initial contact force guided pulmonary vein isolation for paroxysmal atrial fibrillation. (1st September 2017) - Nair, Girish M.; Yeo, Colin; MacDonald, Zachary; Ainslie, Mark P.; Alqarawi, Wael A.; Nery, Pablo B.; Redpath, Calum J.; Sadek, Mouhannad; Spence, Stewart; Green, Martin S.; Birnie, David H.
Abstract: Background and objective: Contact force (CF) sensing is a novel technology used for catheter ablation of atrial fibrillation (AF). We compared the single procedure success of CF‐guided pulmonary vein isolation (PVI) with that of non‐CF guided PVI during a 3‐year (1, 095 days) follow up period and analyzed the pattern of pulmonary vein (PV) reconnection. Methods: A cohort of 167 subjects (68 CF vs. 99 non‐CF) with paroxysmal AF were included in the study. Atrial arrhythmia (AA) recurrence was defined as documented AF, atrial flutter, or atrial tachycardia lasting >30 seconds and occurring after 90 days. Results: Subjects in the CF group showed a statistically nonsignificant improvement in AA free survival compared to those in the non‐CF group (66.2% vs. 51.5%; P value: 0.06). A greater propensity for reconnection was noted around the right‐sided PVs compared to left‐sided PVs related in both catheter ablation groups. For example, in the CF group 36% of right‐sided segments reconnected compared to 16% of left‐sided segments (P value <0.01). Conclusions: A greater propensity for reconnection was noted around the right sided PV segments in both the CF and non‐CF groups. The explanation for this finding was related to greater catheter instability around the right sided veins. Further research is needed to explore the utility of a "real‐time" composite indicator that includes RF energy, CF and catheter stability in predicting transmural lesion formation during catheter ablation.